Can an economically struggling university bolster community engagement as a learning city? Exploring one university initiative in Malawi - Nkhoma, N.M. (South African Journal of Higher Education, 2018)
There is growing need to link universities and their cities in Africa. Yet current research paints a picture that the development relationships between universities and learning cities do not appear to have functioned sustainably in the African contexts. This paper draws from UNESCO guidelines for a learning city to analyze one university efforts of linking community engagement that bolsters a learning city initiative. The case is based on empirical data with a total of 16 actors in community engagement that included deans, heads of departments, faculty in general and university administrators. The evidence, suggested that rather than a formalized and centralized approach, the current university case on the contrary employs an open-ended and ad-doc systems that still bring to the fore the agenda for a learning city. The paper concludes with a call for alternative ways to structure partnerships that do not always structure bureaucratic approaches in poorly resourced universities.